46 xy ovotesticular disorder: A rare case report with review of literature - Bhati Meenal; Gothwal Meenakshi; Singh Pratibha; Yadav Garima; Kathuria Priyanka; Elhence Poonam (Wolters Kluwer Medknow Publications, 2021)
Ovotesticular disorder represents 10% of cases of disorder of sex development characterized by the presence of both ovarian and testicular tissue in the same individual, with karyotype 46 XY being a rare sex chromosomal abnormality. We report the case of a 16-year-old person, who is reared as female, with a complaint of primary amenorrhea along with lack of secondary sexual characteristics, karyotype 46 XY. Prophylactic bilateral gonadectomy was done, and histopathological examination of bilateral gonads revealed ovarian stroma with a few Sertoli cell line tubules suggestive of bilateral ovotestis; hence, we concluded and framed our diagnosis of ovotesticular disorder.